2017
DOI: 10.1111/rec.12589
|View full text |Cite
|
Sign up to set email alerts
|

Sagebrush treatments influence annual population change for greater sage‐grouse

Abstract: Vegetation management practices have been applied worldwide to enhance habitats for a variety of wildlife species. Big sagebrush (Artemisia tridentata spp.) communities, iconic to western North America, have been treated to restore herbaceous understories through chemical, mechanical, and prescribed burning practices thought to improve habitat conditions for greater sage‐grouse (Centrocercus urophasianus) and other species. Although the response of structural attributes of sagebrush communities to treatments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…In Wyoming sagebrush communities highly altered by invasive annual grasses and grazing, negative effects of wildfire have been documented for crucial sage-grouse habitat characteristics, although effects vary depending a number of factors including elevation, sagebrush community type, relative resistance and resilience to fire, time since fire, and prefire site conditions (Nelle and others, 2000;others, 2015, Bates andothers, 2017). Negative effects of wildfire on sagegrouse are largely consistent with previous studies and include altered habitat selection, vital rates, and population trends (Coates and others, 2015(Coates and others, , 2016e, 2017aSmith and Beck, 2017). The findings here support existing concerns and planning efforts to reduce the threat of wildfire to sage-grouse (see U.S.…”
Section: Potential Management Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…In Wyoming sagebrush communities highly altered by invasive annual grasses and grazing, negative effects of wildfire have been documented for crucial sage-grouse habitat characteristics, although effects vary depending a number of factors including elevation, sagebrush community type, relative resistance and resilience to fire, time since fire, and prefire site conditions (Nelle and others, 2000;others, 2015, Bates andothers, 2017). Negative effects of wildfire on sagegrouse are largely consistent with previous studies and include altered habitat selection, vital rates, and population trends (Coates and others, 2015(Coates and others, , 2016e, 2017aSmith and Beck, 2017). The findings here support existing concerns and planning efforts to reduce the threat of wildfire to sage-grouse (see U.S.…”
Section: Potential Management Implicationssupporting
confidence: 88%
“…Understory vegetation (either forbs or perennial grass species) generally increased after sagebrush manipulation, but the response of sage-grouse to treatments varied, perhaps due in part to site-specific ecological variability (Dahlgren and others, 2015;Baxter and others, 2017;Smith and Beck, 2017). Two of these studies found potential benefits of sagebrush manipulation treatments (Dahlgren and others, 2015;Baxter and others, 2017).…”
Section: Sagebrush Manipulation and Understory Restorationmentioning
confidence: 99%
“…This could include large‐scale management experiments or observational studies of actual management actions (Walters and Holling 1990). Fortunately, such investigations are increasingly common (Monroe et al 2017, Smith and Beck 2018, Smith et al 2018 b , Olsen 2019). For example, recent management studies have affirmed the effectiveness of watershed‐scale restoration of conifer‐invaded sagebrush rangelands (Severson et al 2017, Olsen 2019) but have failed to demonstrate clear benefits of managing fine‐scale vegetation structure, e.g., via grazing management (Smith et al 2018 b ) or other treatments (Smith and Beck 2018) intended to increase herbaceous understory cover.…”
Section: Discussionmentioning
confidence: 99%
“…Second, inference from fine‐scale habitat studies may be wholly inadequate to predict outcomes of large‐scale management manipulations on vital rates of populations (Bro et al 2004). With few exceptions (Smith and Beck 2018, Smith et al 2018 b ), effects of extensive vegetation manipulation on sage‐grouse demography are poorly studied. Habitat management guidelines and monitoring assessments thus rest on the assumption that fine‐scale habitat relationships scale up to predict effects of manipulating vegetation at management scales (e.g., pastures, ranches, allotments; Fig.…”
mentioning
confidence: 99%
“…When surface disturbance was maintained after the initial perturbation and associated with existing infrastructure, we termed it press disturbance (i.e., disturbance sustained after initial disturbance and associated with existing energy infrastructure and human activity; Morrison et al 2008). Pulse disturbance, in contrast, is disturbance that is not sustained after an initial perturbation (e.g., fire and mechanical or chemical sagebrush treatments; Smith and Beck 2018) and often originates from a natural process such as wildfire (Morrison et al 2008). Many researchers have focused exclusively on pulse disturbances such as sagebrush treatments and fire.…”
mentioning
confidence: 99%